Analyzing the Influence of Altitudinal Gradients on Clove Physiology and Yield in the Menoreh Highlands - Avianto, Yovi; Pratama, Ananta Bayu; Noviyanto, Amir; Fauzi, Firman Rahmat (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Clove (Syzygium aromaticum) is a significant industrial crop commodity in Indonesia whose yield and essential oil quality are influenced by altitude. Variations in altitude lead to differences in microclimatic conditions, which in turn affect plant physiological activities and productivity. This study aimed to investigate the impact of altitude on the physiological activity, yield, and essential oil content of clove plants. The research was conducted in the lower (345 m asl), middle (612 m asl), and upper (872 m asl) zones of the Menoreh Highlands from March to August 2022. Results indicated that altitude significantly influenced microclimatic conditions, thereby affecting the physiological status and yield of clove plants. The middle zone exhibited optimal physiological performance and flower yield, with a balanced rate of photosynthesis and transpiration. Higher proline levels in the lower and upper zones suggested temperature stress, which reduced photosynthetic rate and yield. Essential oil production and eugenol content were also influenced by altitude, with the middle zone yielding the highest oil volume, although eugenol content was higher in the upper zone. Correlation analysis revealed that temperature and relative humidity were the dominant factors determining clove yield and quality.